Yoga: A nonpharmacological approach against current pandemic of Coronavirus Disease-19 - Ankur Kumar Tanwar; Sujata Rajan (Wolters Kluwer Medknow Publications, 2020)
Introduction: In this current era of the pandemic, when the Covid-19 pandemic rapidly spread across the world, the population at a large scale suffered from fear, worry, and certain concern regarding himself/herself as well as for their families especially adults and children. A significant level of stress also developed in health care providers. Many people all over the world are suffering from loneliness, anxiety, and disturbed mental health issues during lockdown, quarantines, and isolation. Mental health is one of the important factors for overall health. No vaccination or treatment available for COVID-19 till today. The only approach is the preventive and promotive approach. Psychological issues also hamper our physical health and level of immunity. Objective: In this study, an attempt has been made to critically review the role of yoga against the current pandemic. Data Source and Review Methods: References are searched from various authoritative texts and worldwide accepted scientific databases concerning the effect of yoga in the different body systems, immune system as well as on mental health. Result: The psychophysical approach which helps in reducing the mental issue maintains mental health and reduces stress as well as boosts our immunity against communicable diseases like COVID-19 is Yoga. Discussion: Yoga is cost-effective, may be practiced as a self-care treatment against physical and mental health issues, enhance self-efficacy and self-confidence. Yoga may be effective as a supportive adjunct in some medical conditions. Conclusion: This review summarizes the effects of yoga interventions against the current pandemic as well as helps to understand the preventive and health promotive aspect of yoga on various components of mental and physical health.